The role of intercellular communication in diabetic nephropathy - Wang, Bihan; Xiong, Yonghong; Deng, Xinqi; Wang, Yunhao; Gong, Siyuan; Yang, Songyuan; Yang, Baichuan; Yang, Yuhang; Leng, Yan; Li, Wenyuan; Li, Wei (Frontiers in Immunology, 2024)
Diabetic nephropathy, a common and severe complication of diabetes, is the leading cause of end-stage renal disease, ultimately leading to renal failure and significantly affecting the prognosis and lives of diabetics worldwide.However, the complexity of its developmental mechanisms makes treating diabetic nephropathy a challenging task, necessitating the search for improved therapeutic targets. Intercellular communication underlies the direct and indirect influence and interaction among various cells within a tissue. Recently, studies have shown that beyond traditional communication methods, tunnel nanotubes, exosomes, filopodial tip vesicles, and the fibrogenic niche can influence pathophysiological changes in diabetic nephropathy by disrupting intercellular communication. Therefore, this paper aims to review the varied roles of intercellular communication in diabetic nephropathy, focusing on recent advances in this area.